The role of Islamic Educational Institutions: formal, informal, non-formal - Achmad Dahlan Muchtar; Bahaking Rama; Aisyah Suryani (Universitas Muhammadiyah Enrekang, 2024)
The purpose of this study is to discuss the functions of educational institutions, especially Islamic education, both formal, informal and non-formal. This research uses literature study research. Data is collected through literature studies that are in line with the discussion. The results of this study indicate that the purpose of Islamic education is to create people who are aware of their God. Islamic education can be pursued in three ways in accordance with Law No. 20 of 2003 on the National Education System, namely; (1) Formal ways such as, MI, MTs, MA, and Islamic Universities, (2) Non-formal ways such as, Book Reading Training Institutions, TPQ, TPA, and so on, (3) Informal ways such as, Family Education and Community Education. It is not enough to develop the world of education through formal channels alone, but these three channels must work together to develop the world of education. One of the reasons for this is the increasing number of young people who are unable to continue their education. Employment, especially in the private sector, has developed quite rapidly and more than the development of the public sector